Synthesis and characterizations of NiTiO(3) nanoparticles prepared by the sol-gel process - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Mandale, A. B.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2008)
Nanocrystalline nickel titanate (NiTiO(3)) composite powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 750 degrees C for 2 h in air. The results revealed that a pure hexagonal phase of NiTiO(3) could be obtained at the low temperature of 750 degrees C. The phase evolution of NiTiO(3) was investigated by X-ray diffraction patterns, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. Particle size and morphology were studied by transmission electron microscopy.
Keywords: Nanoparticles; nickel titanate; sol-gel process